2008
DOI: 10.1016/j.febslet.2008.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Specific reaction of α,β‐unsaturated carbonyl compounds such as 6‐shogaol with sulfhydryl groups in tubulin leading to microtubule damage

Abstract: 6-Shogaol and 6-gingerol are ginger components with similar chemical structures. However, while 6-shogaol damages microtubules, 6-gingerol does not. We have investigated the molecular mechanism of 6-shogaol-induced microtubule damage and found that the action of 6-shogaol results from the structure of a,b-unsaturated carbonyl compounds. a,b-Unsaturated carbonyl compounds such as 6-shogaol react with sulfhydryl groups of cysteine residues in tubulin, and impair tubulin polymerization. The reaction with sulfhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…The analyses in (a) and (b) were performed three times with similar results and a representative image is shown abrogation of cell cycle checkpoint proteins and spindle assembly checkpoint proteins. Together with results reported by a previous study indicating that 6-shogaol caused microtubule damage through specific reaction with sulfhydryl groups in tubulin [19], we propose here that shogaols induce aberrant mitosis through at least two mechanisms: (1) direct targeting of microtubules, and (2) indirect perturbation of the proper functioning of the mitotic spindle through interference of cell cycle and spindle assembly checkpoint proteins. While it is acknowledged that further work needs to be performed to fully elucidate the exact molecular target(s) of shogaols, this study has thrown light on the structure-activity relationship of naturally-occurring shogaols, where 4-and 6-shogaol possessing short carbon chain lengths were found to exhibit in vitro cytotoxicity in submicromolar concentrations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The analyses in (a) and (b) were performed three times with similar results and a representative image is shown abrogation of cell cycle checkpoint proteins and spindle assembly checkpoint proteins. Together with results reported by a previous study indicating that 6-shogaol caused microtubule damage through specific reaction with sulfhydryl groups in tubulin [19], we propose here that shogaols induce aberrant mitosis through at least two mechanisms: (1) direct targeting of microtubules, and (2) indirect perturbation of the proper functioning of the mitotic spindle through interference of cell cycle and spindle assembly checkpoint proteins. While it is acknowledged that further work needs to be performed to fully elucidate the exact molecular target(s) of shogaols, this study has thrown light on the structure-activity relationship of naturally-occurring shogaols, where 4-and 6-shogaol possessing short carbon chain lengths were found to exhibit in vitro cytotoxicity in submicromolar concentrations.…”
Section: Discussionsupporting
confidence: 88%
“…For example, studies investigating the shogaols' mechanism of apoptosis have reported that 6-and 8-shogaol induce caspase-dependent apoptosis through reactive oxygen species production and disruption of mitochondrial transmembrane potential [16][17][18]. A previous study by Ishiguro et al [19] has provided evidence that 6-shogaol impairs tubulin polymerization through direct targeting of the cysteine residues in b-tubulin. While the findings support G 2 /M arrest as a cellular outcome, we postulate that there may be additional upstream cellular events at work that cause the halt at G 2 /M stage and subsequently induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…60 In fact, 6S can easily react with cysteine as a Michael reaction acceptor. 24 Cysteine residues of tubulin 61 and TRPA1, 62 and even serine residues of eIF2α 63 and Akt1, 64 are modified by 6S. Further study is warranted to pinpoint the sensor cysteines in Keap1 modified by 6S and the structure–activity relationship of shogaols in Keap1 modification.…”
Section: Discussionmentioning
confidence: 99%
“…Ginger, owing to its functional ingredients like [6]-gingerol, [6]-shogaol, [6]paradol, and zerumbone, exhibits anti-inflammatory and antitumorigenic activities (Jeong et al, 2009;Hung et al, 2009). Ginger and its bioactive molecules are effective in controlling the extent of colorectal, gastric, ovarian, liver, skin cancers (Ishiguro et al, 2008;Sung et al, 2008;Brown et al, 2009;Kim et al, 2009;Jeong et al, 2009). Some recent works related to anticancer perspectives have been presented in Table 3.…”
Section: Cancer Insurgence and Gingermentioning
confidence: 99%